Impact of Fidaxomicin De-Restriction on Clostridioides difficile Episodes in Hospitalized Pediatric Cellular Therapy Patients - Andrew Karnaze; Darra Drucker; Regina Orbach; Leila C Posch (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Pediatric patients undergoing cellular therapy (CT) with hematopoietic cell transplantation (HCT) or chimeric antigen receptor T-cell (CAR-T) therapy are vulnerable to Clostridioides difficile infection (CDI). Recent guidelines recommend fidaxomicin treatment for first and recurrent uncomplicated CDI episodes in this population, though pediatric real-world data is limited. Fidaxomicin is narrower spectrum, dosed less frequently, and can be used for shorter durations versus enteral vancomycin. In 2023, Children’s Hospital Los Angeles (CHLA) updated hospital CDI guidelines, allowing CT providers to order fidaxomicin without approval from the antimicrobial stewardship program. This study evaluated the impact of this intervention on CDI episodes in hospitalized CT patients. Methods Data were extracted for patients admitted to the CHLA HCT unit with CDI in the pre- (Nov 2021-Nov 2023) and post-intervention (Dec 2023-Sep 2025) periods. De-restriction of fidaxomicin was implemented 12/1/2023. Episodes were excluded if fulminant, patient was transferred before end of therapy (EOT), or if patient had a preceding CDI in the prior 6 months. The primary outcomes were CDI treatment choice and cure rates. Secondary outcomes included CDI risk factors, change in therapy, recurrence rate, and concurrent positive stool results. Descriptive statistics were performed. Results There were 20 CDI episodes in the pre- and 24 in the post-intervention period. Baseline characteristics and CDI risk factors were similar (Table 1). Most patients underwent allogeneic HCT for malignancy, and most CDI occurred within 10 days of CT. All but 1 patient had preceding antibiotic exposure. Initial CDI treatment was enteral vancomycin in most patients pre- (90%) and post-intervention (79.2%) (Table 2). Intravenous (IV) metronidazole was the second most common initial treatment, and the most frequent drug when therapy was changed. Fidaxomicin use was uncommon. Clinical cure was achieved in 85% vs 75% of episodes, and 8-week recurrence was rare, occurring in 5% vs 8.3% of episodes pre- and post-intervention. Conclusion Despite de-restriction, use of fidaxomicin in cellular therapy patients at CHLA remains uncommon versus enteral vancomycin. Providers were more likely to change therapy to a less optimal second treatment (IV metronidazole), mainly for oral drug intolerance. Additional education and a CT population-specific CDI guideline are needed to optimize treatment. Limitations include low sample size, lack of C. difficile toxin PCR testing, and possible underestimation of recurrences due to 8-week follow up period. Future studies will assess outpatient CDI episodes and treatments used for CT patients with recurrent CDI episodes within 3-6 months.